Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the problem, let's start by clearly outlining both parts of the problem and their step-by-step solutions.
### Part (a): Expanding [tex]\((2 - 3x)^4\)[/tex]
First, we need to expand [tex]\((2 - 3x)^4\)[/tex]. We can use the binomial theorem for this expansion. The binomial theorem states:
[tex]\[ (a - b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} (-b)^k \][/tex]
Here, [tex]\(a = 2\)[/tex], [tex]\(b = 3x\)[/tex], and [tex]\(n = 4\)[/tex].
[tex]\[ (2 - 3x)^4 = \sum_{k=0}^{4} \binom{4}{k} (2)^{4-k} (-3x)^k \][/tex]
Let's compute each term one by one:
1. [tex]\(k = 0\)[/tex]
[tex]\[ \binom{4}{0} (2)^{4-0} (-3x)^0 = 1 \cdot 2^4 \cdot (3x)^0 = 1 \cdot 16 \cdot 1 = 16 \][/tex]
2. [tex]\(k = 1\)[/tex]
[tex]\[ \binom{4}{1} (2)^{4-1} (-3x)^1 = 4 \cdot 2^3 \cdot (-3x) = 4 \cdot 8 \cdot (-3x) = 4 \cdot 8 \cdot (-3x) = -96x \][/tex]
3. [tex]\(k = 2\)[/tex]
[tex]\[ \binom{4}{2} (2)^{4-2} (-3x)^2 = 6 \cdot 2^2 \cdot (9x^2) = 6 \cdot 4 \cdot 9x^2 = 216x^2 \][/tex]
4. [tex]\(k = 3\)[/tex]
[tex]\[ \binom{4}{3} (2)^{4-3} (-3x)^3 = 4 \cdot 2 \cdot (-27x^3) = 4 \cdot 2 \cdot (-27x^3) = -216x^3 \][/tex]
5. [tex]\(k = 4\)[/tex]
[tex]\[ \binom{4}{4} (2)^{4-4} (-3x)^4 = 1 \cdot 1 \cdot 81x^4 = 81x^4 \][/tex]
Combining these terms, we get:
[tex]\[ (2 - 3x)^4 = 16 - 96x + 216x^2 - 216x^3 + 81x^4 \][/tex]
Thus, the coefficients of the expansion are [tex]\(16\)[/tex], [tex]\(-96\)[/tex], [tex]\(216\)[/tex], [tex]\(-216\)[/tex], and [tex]\(81\)[/tex].
### Part (b): Finding [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]
Next, we need to determine the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] given that the sum of the first three terms in ascending powers of [tex]\(x\)[/tex] in the expansion of [tex]\((2 - 3x)^4\left(1 + \frac{a}{x}\right)\)[/tex] is [tex]\(\frac{32}{x} + b + cx\)[/tex].
First, consider the product [tex]\((2 - 3x)^4 \cdot \left(1 + \frac{a}{x}\right)\)[/tex]:
[tex]\[ [(2 - 3x)^4] \cdot \left(1 + \frac{a}{x}\right) \][/tex]
We know the expansion of [tex]\((2 - 3x)^4\)[/tex] and we will multiply each term by [tex]\(\left(1 + \frac{a}{x}\right)\)[/tex]. We focus on the sum of the first three terms in ascending powers of [tex]\(x\)[/tex].
The term for [tex]\(x^{-1}\)[/tex] comes from:
1. [tex]\(16 \times \frac{a}{x} = \frac{16a}{x}\)[/tex]
Matching this with [tex]\(\frac{32}{x}\)[/tex], we get:
[tex]\[ \frac{16a}{x} = \frac{32}{x} \implies 16a = 32 \implies a = 2 \][/tex]
For the constant term:
1. From [tex]\((2 - 3x)^4\)[/tex], the term is [tex]\(16\)[/tex].
2. No contribution from the [tex]\( \frac{a}{x} \)[/tex] portion because there is no [tex]\( \frac{1}{x} \)[/tex] in the constant term.
Therefore, [tex]\(b = 16\)[/tex].
For the [tex]\(x\)[/tex] coefficient term:
1. From [tex]\((2 - 3x)^4\)[/tex], the term is [tex]\(-96x\)[/tex].
2. From [tex]\(16 \times \frac{2}{x}\)[/tex], this is not contributing because it would result in a constant.
Combining these, we get [tex]\( b = 16\)[/tex].
From the expansion and comparison, we got:
[tex]\[ c = -96 \][/tex]
Thus, the values of each of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] are:
[tex]\[ a = 2, \quad b = 16, \quad c = -96 \][/tex]
These were found to closely match the results calculated.
### Part (a): Expanding [tex]\((2 - 3x)^4\)[/tex]
First, we need to expand [tex]\((2 - 3x)^4\)[/tex]. We can use the binomial theorem for this expansion. The binomial theorem states:
[tex]\[ (a - b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} (-b)^k \][/tex]
Here, [tex]\(a = 2\)[/tex], [tex]\(b = 3x\)[/tex], and [tex]\(n = 4\)[/tex].
[tex]\[ (2 - 3x)^4 = \sum_{k=0}^{4} \binom{4}{k} (2)^{4-k} (-3x)^k \][/tex]
Let's compute each term one by one:
1. [tex]\(k = 0\)[/tex]
[tex]\[ \binom{4}{0} (2)^{4-0} (-3x)^0 = 1 \cdot 2^4 \cdot (3x)^0 = 1 \cdot 16 \cdot 1 = 16 \][/tex]
2. [tex]\(k = 1\)[/tex]
[tex]\[ \binom{4}{1} (2)^{4-1} (-3x)^1 = 4 \cdot 2^3 \cdot (-3x) = 4 \cdot 8 \cdot (-3x) = 4 \cdot 8 \cdot (-3x) = -96x \][/tex]
3. [tex]\(k = 2\)[/tex]
[tex]\[ \binom{4}{2} (2)^{4-2} (-3x)^2 = 6 \cdot 2^2 \cdot (9x^2) = 6 \cdot 4 \cdot 9x^2 = 216x^2 \][/tex]
4. [tex]\(k = 3\)[/tex]
[tex]\[ \binom{4}{3} (2)^{4-3} (-3x)^3 = 4 \cdot 2 \cdot (-27x^3) = 4 \cdot 2 \cdot (-27x^3) = -216x^3 \][/tex]
5. [tex]\(k = 4\)[/tex]
[tex]\[ \binom{4}{4} (2)^{4-4} (-3x)^4 = 1 \cdot 1 \cdot 81x^4 = 81x^4 \][/tex]
Combining these terms, we get:
[tex]\[ (2 - 3x)^4 = 16 - 96x + 216x^2 - 216x^3 + 81x^4 \][/tex]
Thus, the coefficients of the expansion are [tex]\(16\)[/tex], [tex]\(-96\)[/tex], [tex]\(216\)[/tex], [tex]\(-216\)[/tex], and [tex]\(81\)[/tex].
### Part (b): Finding [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]
Next, we need to determine the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] given that the sum of the first three terms in ascending powers of [tex]\(x\)[/tex] in the expansion of [tex]\((2 - 3x)^4\left(1 + \frac{a}{x}\right)\)[/tex] is [tex]\(\frac{32}{x} + b + cx\)[/tex].
First, consider the product [tex]\((2 - 3x)^4 \cdot \left(1 + \frac{a}{x}\right)\)[/tex]:
[tex]\[ [(2 - 3x)^4] \cdot \left(1 + \frac{a}{x}\right) \][/tex]
We know the expansion of [tex]\((2 - 3x)^4\)[/tex] and we will multiply each term by [tex]\(\left(1 + \frac{a}{x}\right)\)[/tex]. We focus on the sum of the first three terms in ascending powers of [tex]\(x\)[/tex].
The term for [tex]\(x^{-1}\)[/tex] comes from:
1. [tex]\(16 \times \frac{a}{x} = \frac{16a}{x}\)[/tex]
Matching this with [tex]\(\frac{32}{x}\)[/tex], we get:
[tex]\[ \frac{16a}{x} = \frac{32}{x} \implies 16a = 32 \implies a = 2 \][/tex]
For the constant term:
1. From [tex]\((2 - 3x)^4\)[/tex], the term is [tex]\(16\)[/tex].
2. No contribution from the [tex]\( \frac{a}{x} \)[/tex] portion because there is no [tex]\( \frac{1}{x} \)[/tex] in the constant term.
Therefore, [tex]\(b = 16\)[/tex].
For the [tex]\(x\)[/tex] coefficient term:
1. From [tex]\((2 - 3x)^4\)[/tex], the term is [tex]\(-96x\)[/tex].
2. From [tex]\(16 \times \frac{2}{x}\)[/tex], this is not contributing because it would result in a constant.
Combining these, we get [tex]\( b = 16\)[/tex].
From the expansion and comparison, we got:
[tex]\[ c = -96 \][/tex]
Thus, the values of each of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] are:
[tex]\[ a = 2, \quad b = 16, \quad c = -96 \][/tex]
These were found to closely match the results calculated.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.